Alcohol's involvement in an array of harms to intimate partners - Laslett, Anne-Marie; Jiang, H.; Room, R. (Wiley-Blackwell Publishing Ltd., 2016)
Introduction: Harms from intimate partners' (IP) drinking range from frustration because the partner has not performed their role to assault. Aim: To describe the prevalence and persistence of alcohol-related harms to IPs and assess which respondents are more likely to report discontinuation of this harm. Design and methods: Cross-sectional (n=2649) and follow-up (n=1106) alcohol's harm to others telephone surveys in 2008 and 2011 (response rates of 35% and 15% of the original sample respectively) were used to elicit harms to respondents from their IP's drinking (by gender and relationship). To examine discontinuation, a sub-sample of 83 respondents was analysed in detail. Results: A total of 6.7% of Australians were negatively affected by an IP's drinking in 2008. Women were more likely to report harm than men from an IP's drinking. Of the 1106 respondents who completed both surveys, the majority (90%) reported no harm from IPs although 3% reported harm in both surveys. No significant correlates of discontinuation of harm were identified. Discussion: Many Australian relationships are affected in a range of ways because of the drinking of their IPs. A minority of respondents were affected by their IP's drinking, yet over half (57%) of those harmed in 2008 continued to experience harm in 2011. Additionally, half (46.9%) of those who were not harmed in 2008 but did live with a heavy drinking IP did go on to be harmed in 2011. More research on the role of alcohol-related harm from IPs with larger samples is required to examine predictors of change.